Military operation «Socorro»: Fifty years later - Taype Castillo, Jaime Miguel (2021)
On the afternoon of May 31, 1970, an earthquake and avalanche disappeared the Yungay city, in Ancash. This tragic event, like a war, required the intervention of the Peruvian Armed Forces through a military operation to rescue the survivors, remove debris and rebuild affected populations. The objective of this research is to describe the intervention of the peruvian military in non-war or political events, but in actions to help the population affected by the natural disaster. For this, military sources have basically been used, the same ones that provide important information but that almost always go unnoticed among the existing investigations on the subject.